Protein quality control of N-methyl-D-aspartate receptors - Benske, Taylor M.; Mu, Ting-Wei; Wang, Ya-Juan (Frontiers in Cellular Neuroscience, 2022)
N-methyl-D-aspartate receptors (NMDARs) are glutamate-gated cation channels that mediate excitatory neurotransmission and are critical for synaptic development and plasticity in the mammalian central nervous system (CNS). Functional NMDARs typically form via the heterotetrameric assembly of GluN1 and GluN2 subunits. Variants within GRIN genes are implicated in various neurodevelopmental and neuropsychiatric disorders. Due to the significance of NMDAR subunit composition for regional and developmental signaling at synapses, properly folded receptors must reach the plasma membrane for their function. This review focuses on the protein quality control of NMDARs. Specifically, we review the quality control mechanisms that ensure receptors are correctly folded and assembled within the endoplasmic reticulum (ER) and trafficked to the plasma membrane. Further, we discuss disease-associated variants that have shown disrupted NMDAR surface expression and function. Finally, we discuss potential targeted pharmacological and therapeutic approaches to ameliorate disease phenotypes by enhancing the expression and surface trafficking of subunits harboring disease-associated variants, thereby increasing their incorporation into functional receptors.